On continuity of $KC$-functions with values in Ceder plane - Maslyuchenko, V.K.; Myronyk, O.D. (Carpathian Mathematical Publications, 2014)
We show that the Ceder plane $\mathbb{M}$ is a $σ$-metrizable space, which does not have a development. For every quasicontinuous mapping $f:X→\mathbb{M}$ the continuity point set $C(f)$ is residual. We investigate the continuity point set $C(f)$ of a mapping $f:X× Y→ \mathbb{M}$, which is quasicontinuous with respect to the first variable and continuous with respect to the second one.